Ts. Dr. Mohd Azrul Hisham creates a tool to monitor physiological parameters of babys health - Safriza, Baharuddin; Nur Hartini, Mohd Hatta (2021)
GAMBANG, 2 August 2021 - A researcher and Senior Lecturer from College of Engineering (KKEJ), Universiti Malaysia Pahang (UMP), Ts. Dr. Mohd Azrul Hisham Mohd Adib, 38, invented a device to monitor the physiological parameters of a baby’s health or known as the InfaWrap Device.